Pengaruh Model Problem Based Learning (PBL) terhadap Hasil Belajar Peserta Didik Kelas X MIPA SMA Negeri 6 Makassar (Studi pada Materi Pokok Larutan Elektrolit dan Nonelektrolit) - Muhammad Ismail Alwi; Sugiarti Sugiarti; Sudding Sudding (ChemEdu, 2022)
This research is quasi-experimental research that aims to know the effect of the problem based learning model (PBL) towards the learning outcomes of the students of class X MIPA SMA Negeri 6 Makassar on the subject matter of electrolyte and nonelectrolyte solution, with posttest only group design. The population is the student of class X MIPA SMA Negeri 6 Makassar consisting of six classes. Sample was randomly selected and X MIPA4 as the experimental class and X MIPA5 class as the control. The experimental class was taught by using the PBL model while the control class was taught with conventional learning model. The learning outcomes data is taken by giving posttest. Learning outcomes data are processed in descriptive statistics and inferential statistics. Descriptive statistical analysis showed that experimental class has higher learning outcomes completeness than control class with 74.29% and 51.52%. The test results for inferential statistical analysis hypotheses using the Mann Whitney test with α = 0.05 obtained Zcount (5.90) > Ztable (1.64). Based on these α values, it shows that there is an effect of the PBL model on the learning outcomes of students of class X MIPA SMA Negeri 6 Makassar on the study of electrolyte and nonelectrolyte solution.